The Public Leadership Ethics: A Study at Universitas Islam Syekh-Yusuf, Tangerang, Indonesia - Muhammad Rosul Asmawi (UNIVERSITAS ISLAM SYEKH YUSUF, 2025)
Public leadership ethics serves as a crucial foundation for establishing fair, transparent, and accountable governance, particularly within higher education institutions grounded in Islamic values. In the context of Islamic universities, leaders are expected not only to demonstrate administrative professionalism but also to embody moral and spiritual integrity. This study aims to analyze the practice of public leadership ethics at Universitas Islam Syekh-Yusuf (UNIS) Tangerang, focusing on the ethical values upheld by university leaders, the dynamics of decision-making, and the challenges encountered in implementing these ethical principles. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with university leaders, observations, and institutional document analysis. The findings reveal that values such as honesty, responsibility, justice, and accountability serve as the core foundations of leadership at UNIS. Nevertheless, several ethical challenges arise in practice, particularly in strategic decision-making processes involving both institutional and individual interests. This study provides a theoretical contribution to the development of a public leadership model rooted in Islamic ethics, while also offering practical implications for improving governance within higher education institutions. It is expected that the results of this research will serve as a reference for strengthening an ethical and accountable organizational culture in Islamic universities. ?